Helicobacter pylori infection and its impact on psoriasis: a systematic review and meta-analysis - Yan, Yijiao; Deng, Wenhui; Shi, Chengzhi; Xie, Jiaxin; Sui, Daoshun (Frontiers in Medicine, 2024)
Introduction Psoriasis is a chronic skin condition characterized by immune-mediated inflammation. Recent research suggests a possible interaction between Helicobacter pylori infection and the immunopathogenesis of psoriasis. However, over the past 5 years, no significant new evidence has clarified the relationship between H. pylori and skin diseases. This study aimed to determine the relationship between H. pylori infection and psoriasis through a systematic review and meta-analysis. Methods We searched for articles published in databases including PubMed, Embase, the China National Knowledge Infrastructure, and Web of Science up to January 1, 2024. Statistical analyses were conducted using Review Manager 5.3 and Stata 12.0 software. Results Our search yielded 271 papers. After rigorous screening by multiple reviewers, 15 studies involving 2,427 individuals were included. The odds ratio for H. pylori infection was significantly higher in the psoriasis group than in the control group (odds ratio = 1.94, 95% confidence interval: 1.40–2.68, p < 0.0001). Subgroup analysis revealed no significant differences in H. pylori infection rates between Asia and Europe. The type of study also did not significantly affect infection rates. The enzyme-linked immunosorbent assay detected H. pylori infection at a significantly higher rate than the breath test. Furthermore, the prevalence of H. pylori infection differed significantly between patients with moderate-to-severe psoriasis and those with mild psoriasis. Conclusion Our findings suggest a relationship between psoriasis and H. pylori infection, with variations observed based on geography, testing methods, and disease severity. These findings hold significant potential for guiding clinical practice. Systematic review registration http://www.crd.york.ac.uk/, identifier CRD42022359427.